Probing ultraweak in-plane magnetic anisotropy within a two-dimensional layered antiferromagnet - Yijie Fan; Yihong Xu; Renji Bian; Ruan Zhang; Junning Mei; Jiaxin Wu; Binghe Xie; Shuangxing Zhu; Yu Chen; Feifan Gu; Ying Liu; Takashi Taniguchi; et al. (Proceedings of the National Academy of Sciences, 2025)
Magnetic anisotropy plays a crucial role in determining the critical behavior and phase transitions in two-dimensional magnetic systems. It is also required for the design of thin-film spintronic devices. Despite its significance, sensing extremely weak anisotropy has proven challenging in van der Waals antiferromagnetic/ferrimagnetic materials. Here, we first employ simulations of micromagnetic energy function in few-layer easy-plane antiferromagnetic systems with a weak additional uniaxial anisotropy and unveil an intriguing even–odd effect closely linked to low-field spin–flop behaviors. We further perform tunneling magneto-conductance measurements on a model 2D antiferromagnetic insulator, CrCl 3 , exhibiting near-ideal easy-plane anisotropy. The magnetic field-controlled tunneling current at low temperature aligns well with simulated in-plane anisotropic spin-configuration, providing direct experimental evidence for detecting magnetic anisotropy field around 1 mT. Our work creates opportunities for finely characterizing magnetic structures and behaviors in 2D antiferromagnetic/ferrimagnetic systems, with potential applications in spintronics such as data storage and magnetic sensing.